Sexual Sensation Seeking, Co-occurring Sex and Alcohol Use, and Sexual Risk Behavior among Adolescents in Treatment for Substance Use Problems - Oshri, Assaf (Am J Addict, 2013)
OBJECTIVE: This study evaluated relations between sexual sensation seeking, co-occurring sex and alcohol use, and sexual risk behaviors (eg, unprotected intercourse and multiple sex partners) among adolescents receiving treatment for substance abuse problems. METHOD: The ethnically diverse sample included 394 adolescents recruited from outpatient treatment (280 males; M(age) = 16.33 years, SD(age) = 1.15). Structural equation modeling (SEM) was used to test direct and indirect paths between sexual sensation seeking and sexual risk behaviors via the frequency of co-occurring sex and alcohol use. Conditional indirect effects by gender were also tested. RESULTS: Analyses identified significant direct and indirect effects from sexual sensation seeking to sexual risk behaviors via co-occurring sex and alcohol. The path from co-occurring sex and alcohol use to unprotected intercourse was significantly stronger among adolescent girls, suggesting a mediation effect moderated by gender. The path from sexual sensation seeking to past year number of partners via co-occurring sex and alcohol was stronger among adolescent boys. However, this gender path difference was not statistically significant. CONCLUSIONS: Selected prevention efforts are needed to promote HIV risk reduction among adolescents in substance abuse treatment. The documented conditional indirect effect for unprotected intercourse suggests that HIV prevention programs should pay special attention to gender-specific patterns of alcohol use and sexual risk behavior when tailoring program content.